ERGONOMIC RISK AND MUSCULOSKELETAL PAIN IN DENTAL PRACTICE - Jakupović, Vedran; Allouch, Alaudin; Bajsman, Anita (Sanamed, 2026)
Objective: Ergonomics in dental practice plays a crucial role in maintaining professional health, as prolonged static postures and repetitive movements significantly increase the risk of work-related musculoskeletal disorders among dental professionals. Understanding ergonomic risk factors and their impact on musculoskeletal health is essential for identifying vulnerable groups and developing effective preventive strategies in dental practice.Aim: The aim of this study was to assess the occurrence of musculoskeletal pain as a manifestation of work-related musculoskeletal disorders among dentists and to analyze its association with demographic characteristics, work habits, and dental specialization.Materials and Methods: This cross-sectional study included 130 dentists from various dental specialties. Data were collected using a structured questionnaire addressing demographic variables, work habits, ergonomic conditions, and the presence of musculoskeletal pain. Descriptive statistical methods were applied, and chi-square tests were used to analyze associations between categorical variables, with statistical significance set at p < 0.05.Results: The results indicated that the majority of participants experienced work-related musculoskeletal disorders, with prevalence increasing with age and length of professional experience. Occupational factors such as prolonged sitting or standing, improper working posture, lack of ergonomic chairs, and insufficient physical activity were significantly associated with the occurrence of work-related musculoskeletal disorders (p < 0.05). A statistically significant association was also observed between dental specialty and the presence of work-related musculoskeletal disorders (χ²(9) = 25.83; p < 0.01). The highest prevalence was reported among specialists in prosthodontics, pediatric dentistry, orthodontics, and endodontics, while lower prevalence was observed among oral surgeons, general dental practitioners, and periodontists.Conclusion: These findings emphasize the importance of implementing ergonomic interventions, regular physical activity, and preventive strategies in dental practice to reduce the occupational risk of work-related musculoskeletal disorders.
Keywords: ergonomics; dentistry; WMSDs; musculoskeletal pain; occupational risk; specialization